Re-Examining Respect for Human Research Participants - Dickert, Neal W. (Kennedy Institute of Ethics journal, 2009)
The demands of respect for persons when conducting clinical research are often reduced to respect for autonomy. In this paper, I re-examine the concept of respect for persons in light of important intuitions from our ordinary language usage of respect. I propose that there are many ways to respect persons as persons and that the core elements of respect for persons are: appreciating what is valuable or important about a person, recognizing the constraints or demands that such a valuation places on one's own conduct, and acting in a way that expresses that recognition. On this account, in addition to autonomous agency, respect demands attention to important subjective experiences, persons' existence as part of communities, and considerations of comportment. This account has important implications for the conduct of clinical research with persons who are autonomous as well as with those who are not. Its implications, however, are different for these two populations, particularly with regard to concerns about well-being.